Comparison of uncoated and coated carbide inserts in end milling of Ti–6Al–4V in terms of surface roughness - Hossain, Mohammad Ishtiaq; Amin, A. K. M. Nurul; Patwari, Muhammed Anayet Ullah; Ginta, Turnad Lenggo (2008)

(untitled)
This paper compares and also optimizes the surface finish in end milling of titanium alloy Ti-6Al-4V using uncoated and PVD TiAlN coated carbide inserts under dry conditions. Response Surface Methodology (RSM) is utilized to develop an efficient mathematical model for surface roughness in terms of cutting speed, feed and axial depth of cut. For this purpose, a number of machining experiments based on factorial design of experiments method are carried out. The Center Composite Design (CCD) surface roughness models have been developed at 95% confidence level. The adequacy of the models has been verified through analysis of variance (ANOVA). Then the RSM models were further coupled with Genetic Algorithm (GA) to optimize the cutting conditions for getting achievable minimum surface roughness. The GA outcomes were further verified by experimental results. It was found that GA results matched successfully with the experimental data. Uncoated carbide insert was stumbled on as a better option than TiAlN coated carbide in terms of surface roughness.